(untitled) - Chodorow, Marvin (New York, 1964)
This book contains detail theoretical treatments of individual tubes, aim at specific details and often fail to set forth the basic principles of microwave electronics in a general manner.
Keywords: Ống lò vi sóng,Microwave tubes